PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA MATERI KPK DAN FPB KELAS IV SD NEGERI 067093 MEDAN HELVETIA - Br Simarmata, Ananta Pratiwi; Dyan Wulan Sari HS; Antonius Remigius Abi; Jhonas Dongoran; Anton Sitepu; Patri Janson Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
His study aims to analyze the effect of the Think Pair Share (TPS) model. The results showed that the average learning outcomes of fourth-grade Mathematics subjects were 84,44 with a good category. Of the 25 students studied, 21 students (84%) met the Minimum Completion Criteria (KKTP), while 4 students (16%) did not meet the KKTP. This study is a type of quantitative research that aims to determine the effect of the Think Pair Share (TPS) model on student learning outcomes in Mathematics subjects in fourth-grade SD Negeri 067093 Medan Helvetia. The population was all fourth-grade students totaling 25 students. The sample was taken based on a total sampling technique of 25 students. Student learning outcomes showed that the average value of fourth-grade students in the pre-test was 57,76 while the post-test value was 84,44. The results of this study indicate that students' Mathematics learning outcomes using the Think Pair Share (TPS) learning model are included in the strong category with a correlation coefficient of 0.963, which means r count (0.369) ≥ r table so Ha is accepted. Furthermore, the hypothesis test showed a calculated t of 8.416, while the t table was 2.060. This proves that the hypothesis is greater than the t table. Therefore, Ho is rejected and Ha is accepted. Therefore, it can be concluded that the Think Pair Share (TPS) model (X) has a positive and significant influence on learning outcomes (Y). This indicates that the Think Pair Share (TPS) model has an effect on students' science learning outcomes. Therefore, all questionnaire instruments in this study are declared reliable and trustworthy, as they have met the minimum requirements.